The New View on fiscal policy and its implications for the European Monetary Union - Atanas Pekanov (Austrian Institute of Economic Research (WIFO), 2018)
The New View on fiscal policy (as coined by Furman 2016) represents a rethinking of the main-stream consensus on the optimal macroeconomic policy mix. It focuses on a reassessment of the relative effectiveness of fiscal policy and its ability to stabilise the economy when monetary policy reaches its limit. This paper aims to present in detail the main principles of the New View as proposed by Furman (2016), to extend them, bring additional theoretical and empirical evidence, as well as concrete policy implications for the architecture of the European Monetary Union. The New View builds upon five core principles: Firstly, fiscal policy is a significant and efficient complement to monetary policy at the zero lower bound on theoretical grounds. Secondly, we take a closer look at the empirical evidence on government spending multipliers in a recession, both in the DSGE and in the VAR literature, and show it points to much higher multipliers than in normal times. Thirdly, we provide evidence to why fiscal space is actually higher than normally perceived in a recession, because fiscal stimuli can pay for themselves by enhancing current growth and potential output. We shortly discuss whether it is not better to have a sustained stimulus rather than a short one and whether enhanced global spillover effects in an environment of insufficient aggregate demand further enhance fiscal policy effectiveness. All of the above arguments point to the welfare enhancing effects of fiscal stimulus during a zero lower bound episode and that an approach, led by the New View, would have delivered better macroeconomic outcomes during the Eurozone crisis. We then discuss what such an approach could mean for a more resilient EMU architecture and for stabilisation mechanisms in the Euro Area.
Keywords: E00; E62; E63; E65; F45; 330; Macroeconomic stabilization; Fiscal policy; Zero lower bound; Business cycle